Important double bond effect on the aggregation behavior of an alkenyl succinic acid derivative - Silva, Oscar Fernando (2016)
The aggregation behavior of 2-(2-decenyl) succinic acid (C10SA) in alkaline aqueous media was extensively studied and found interesting properties. The CMC (critical micelle concentration) is lower than expected for a compound with two carboxylate groups and an alkenyl chain of 10–12 carbon atoms. We identified that among the factors that affect the CMC, the double bond and the arrangement of the carbonyl group play a crucial role. They favor an ease packing of the head group of the surfactant resulting in a reduction of their mutual repulsion in the micelle. This particular conformation influences the solubilization/aggregation behavior and is responsible of the high tendency to self-assembly forming micelles of spherical shape and small size. An important feature of C10SA molecules is their ability to orient the carboxyl groups in a way that allow them been packed in the aggregates and this property may be of interest for many future applications.